Proporsi Potongan Utama Komersial Karkas (Primal Cut) Pada Sapi Brahman Cross - Amri, Ulil (Fakultas Peternakan Universitas Jambi, 2009)
The experiments was conducted to find proportion of primal cut on Brahman Cross Carcass. The experiment was conducted for 6 months in Slaughter house PT.SampiCo Adhi Abbatoir Cibitung Bekasi West Java. A hundred forty nine (imported from Australia) castrated Brahman Cross cattle (steer) were used with 1.5 up to more than 4 years of age and 379 – 622 kg of body weight. The design was randomized block completely design in 3 x 4 factorial design with 3 feedlots and 4 group of body weight and was analysed following GLM procedure with median of smallest quadrat (SAS, 1985 and Montgomery, 1991). The study showed that there was no significant on primal cut weight and its percentage among feedlot. Increase body weight significantly increased weight of primal cut but no proportion of primal cut.